1985
DOI: 10.1507/endocrj1954.32.127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microelectrophoretically applied acetylcholine, noradrenaline, dopamine and serotonin on the discharge of paraventricular oxytocinergic neurones in the rat.

Abstract: The effects of microelectrophoretic applications of neurotransmitter substances and their antagonists on the activity of paraventricular oxytocinergic neurones were studied in urethane anesthetized lactating rats. Oxytocinergic neurones were identified by their antidromic response to the stimulation of the neurohypophysis and by their characteristic high frequency discharge of action potentials approximately 15-20 s before reflex milk ejection. Acetylcholine (ACh) excited the majority (75%) of paraventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…It is unclear how or if DA or 5-HT regulates release of OT in the amygdala, although the paraventricular nucleus, which is the main site for OT synthesis and projection, receives inhibitory 5-HT and DA inputs to the magnocellular OT neurons and these inhibitory systems are activated under stressful conditions such as might occur when faced with an intruder (Honda et al, 1985;Burt, 1993). How much effect these inhibitory systems may ultimately have is questionable given that chronic cocaine administration has been shown to decrease 5-HT's regulation of neuroendocrine responses, including the release of OT (Levy et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear how or if DA or 5-HT regulates release of OT in the amygdala, although the paraventricular nucleus, which is the main site for OT synthesis and projection, receives inhibitory 5-HT and DA inputs to the magnocellular OT neurons and these inhibitory systems are activated under stressful conditions such as might occur when faced with an intruder (Honda et al, 1985;Burt, 1993). How much effect these inhibitory systems may ultimately have is questionable given that chronic cocaine administration has been shown to decrease 5-HT's regulation of neuroendocrine responses, including the release of OT (Levy et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to having OT neurons, fibers and/or receptors, the paraventricular nucleus, hippocampus, amygdala, MPOA and VTA contain DA, 5-HT and NE projections, neurons or receptors (Kimble et al, 1967;Fahrbach et al, 1985;Kendrick et al, 1987;Tribollet et al, 1988;Burt, 1993;Numan, 1994;Pedersen et al, 1994). There is anatomical evidence that OT neurons are in close contact or have synaptic connections with axons of neurons of these three neurotransmitter systems Horie et al, 1993) and that OT system dynamics (release, levels or receptors) can be altered by both cocaine and by manipulation of each of the aforementioned neurotransmitter systems (Rosenberg et al, 1977;Honda et al, 1985;Drago et al, 1986;Giordano et al, 1990;Kovacs et al, 1990;Cunningham et al, 1992;Kendrick et al, 1992;Sarnyai et al, 1992;Hansen, 1994;Van de Kar et al, 1995;Bagdy, 1996;Thomas and Palmiter, 1997;Ji et al, 1998;Onaka and Yagi, 1998). While there is almost no evidence for NE being involved in maternal aggression (Sorenson and Gordon, 1975), both DA and 5-HT systems are implicated as possible systems underlying aggressive behavior (Neckers et al, 1975;Ieni and Thurmond, 1985;Mos et al, 1990;Olivier and Mos, 1992;De Almeida and Lucion, 1994;Moeller et al, 1994;Olivier et al, 1995;Matto et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Clarke et al (231) observed that muscarinic agonists, but not nicotine, mimicked ACh in stimulating OT release, yet nicotinic, rather than muscarinic, antagonists inhibited suckling-induced increases in intramammary pressure. Both nicotinic and muscarinic cholinergic receptors were also implicated in early work by Moss et al (207) showing stimulation of PVN neurosecretory cell activity in response to microiontophoretically applied ACh, and in more recent studies by Honda et al (232), in which PVN OT cells were identified electrophysiologically in lactating rats. In both cases, the effect of ACh was most effectively inhibited by a combination of muscarinic and nicotinic antagonists.…”
Section: Central Actions Of Other Neurotransmitters On Ot Secretionmentioning
confidence: 89%
“…Reports using rodent models have found that serotonin and dopamine can both impact various aspects of the oxytocin system, and given the peptide's likely role in maternal behavior onset and aggression in rodents, gestational uptake inhibition of one or a combination of these systems could subsequently alter these behaviors (Bagdy, 1996;Cunningham et al, 1992;Giordano et al, 1990;Hansen, 1994;Honda et al, 1985;Kendrick et al, 1992;Lubin et al, 2003a,b;Sarnyai and Kovacs, 1994;Van de Kar et al, 1995). Oxytocin has been shown to be extremely important to the onset of maternal behavior, though perhaps not as vital to the maintenance of maternal behavior and evidence suggests it plays a role in maternal aggression as well (Fahrbach et al, 1985;Lubin et al, 2003b;Pedersen et al, 1985Pedersen et al, , 1994Van Leengoed et al, 1987).…”
Section: Introductionmentioning
confidence: 99%